2020
DOI: 10.1007/s11192-020-03475-9
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence-based understanding of introductions of research articles

Abstract: Achieving publications in high-impact journals is a major cornerstone for academic careers in the US and elsewhere in the world. However, apart from novel insights and relevant contributions to the field, there are expectations of editors and reviewers regarding the structure and language of manuscripts that prospective contributors have to adhere to. As these expectations are mostly communicated using best-practice examples, especially international researchers might often wonder how to implement them in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
1
5
0
1
Order By: Relevance
“…(H2) This step appeared as the most frequently incorporated step in the present study for its 100% occurrence in both datasets. This finding resembles the result of prior studies conducted by Amnuai and Wannaruk (2013), Bajwa et al (2020), Joseph et al (2014), and Rahman et al (2017. JELTL (Journal of English Language Teaching and Linguistics), 6(2), 2021 Move 3 step 2: Presenting research questions or hypotheses This move was not utilized in the present corpora.…”
Section: Move 3 Step 1: Announcing Present Research Descriptively And...supporting
confidence: 92%
See 1 more Smart Citation
“…(H2) This step appeared as the most frequently incorporated step in the present study for its 100% occurrence in both datasets. This finding resembles the result of prior studies conducted by Amnuai and Wannaruk (2013), Bajwa et al (2020), Joseph et al (2014), and Rahman et al (2017. JELTL (Journal of English Language Teaching and Linguistics), 6(2), 2021 Move 3 step 2: Presenting research questions or hypotheses This move was not utilized in the present corpora.…”
Section: Move 3 Step 1: Announcing Present Research Descriptively And...supporting
confidence: 92%
“…Many researchers have utilized Swales' model to analyze how genre styles employed in a single specific discourse community: Applied Linguistics (e.g. Ozturk, 2007Ozturk, , 2018Rahman, Darus, & Amir, 2017;Sheldon, 2011), English language teaching (ELT) (Rochma & Triastuti, 2020), Psychology (Loi, 2010), Management (Bajwa, König, & Kunze, 2020). Öztürk (2018), for instance analyzed 50 research article introductions (henceforth RAIs) and unlike Move 1 and Move 3, Move 2 Establishing a niche was found to be obligatory.…”
Section: Introductionmentioning
confidence: 99%
“…Samraj (2002) emphasizes the importance of introductions in setting the stage for the research. Bajwa et al (2020) further underscore the significance of introductions in meeting the expectations of editors and reviewers, particularly in high-impact journals. However, despite recognizing their importance, previous research has identified several limitations in the introductions.…”
Section: Introductionmentioning
confidence: 86%
“…Many studies have explored the key elements of impactful introductions in academic writing. Bajwa et al (2020) emphasize the importance of adhering to the expectations of editors and reviewers, particularly in high-impact journals. Fried et al (2019) highlight the need for an attention-grabbing introduction that provides a roadmap for the paper, builds on existing research, and poses straightforward research questions.…”
Section: Guidelines For Crafting Impactful Introductions With Avoidan...mentioning
confidence: 99%
“…Nevertheless, the increasing pressure to elevate Indonesian scholars' international publication rate is evident. In academic writing, Bajwa et al (2020) note that of all sections, introduction is regarded as one of the most difficult and time-consuming parts to write, even for experienced authors. However, this section still needs to be well-written considering its importance.…”
Section: Introductionmentioning
confidence: 99%